Automation, Global Value Chains and Functional Specialization - Lionel Fontagné; Ariell Reshef; Gianluca Santoni; Giulio Vannelli (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study how technology adoption and changes in global value chain (GVC) integration jointly affect labor shares and business function specialization in a sample of 14 manufacturing industries in 14 European countries in 1999–2011. Our main contribution is to highlight the indirect effect of robotization on relative demand for labor via GVC integration. To do this, we develop a methodology to separately account for robots in the total capital stock. Increases in upstream, forward GVC participation directly reduce labor shares, mostly through reductions in fabrication, but also via management, marketing and R&D business functions. We do not find any direct effects of robot adoption; robotization affects labor only indirectly, by increasing upstream, forward GVC integration. In this sense robotization is "upstream-biased". We also study novel channels through which rapid robotization in China shaped robotization in Europe and, therefore, GVC participation. This highlights an understudied way by which the global integration of China has affected relative demand for labor in its trading partners.
Keywords: E25; F14; F16; O33; 330; labor share; functional specialization; global value chains; upstreamness; technological change; automation; robots